Notch-1 signaling promotes the malignant features of human breast cancer through NF-κB activation. - Li Li (Public Library of Science (PLoS), 2014)
The aberrant activation of Notch-1 signaling pathway has been proven to be associated with the development and progression of cancers. However, the specific roles and the underlying mechanisms of Notch-1 signaling pathway on the malignant behaviors of breast cancer are poorly understood. In this study, using multiple cellular and molecular approaches, we demonstrated that activation of Notch-1 signaling pathway promoted the malignant behaviors of MDA-MB-231 cells such as increased cell proliferation, colony formation, adhesion, migration, and invasion, and inhibited apoptosis; whereas deactivation of this signaling pathway led to the reversal of the aforementioned malignant cellular behaviors. Furthermore, we found that activation of Notch-1 signaling pathway triggered the activation of NF-κB signaling pathway and up-regulated the expression of NF-κB target genes including MMP-2/-9, VEGF, Survivin, Bcl-xL, and Cyclin D1. These results suggest that Notch-1 signaling pathway play important roles in promoting the malignant phenotype of breast cancer, which may be mediated partly through the activation of NF-κB signaling pathway. Our results further suggest that targeting Notch-1 signaling pathway may become a newer approach to halt the progression of breast cancer.